Dampak Dosis Urea terhadap Sifat-sifat Tanah, Populasi Mikroba, dan Produksi Sorgum (Sorghum bicolor L.) pada Tanah Latosol - Bachtiar, Taufiq; Adirianto, Bayu; Hanani, Muftia; Robifahmi, Nur; Flatian, Anggi Nico; Citraresmini, Ania (Universitas Bangka Belitung, 2023)
Urea Fertilizer doses are a significant factor in sorghum production. This research was conducted to study soil characteristics and sorghum production through the applications of urea fertilizer doses in Latosol soil. This research was conducted from May to September 2019 in the KST GA Siwabesy experiment field at Pasar Jumat, South Jakarta. The design used in this study was a randomized block design (CRD) with 4 treatments in the form of fertilizer N doses of 0 kg ha-1, 50 kg ha-1, 100 kg ha-1, and 200 kg ha-1. The results showed that applying N fertilization did not affect soil pH, soil P available, soil organic C, soil N total, C/N ratio, CO2 content, and soil nitrate content. N fertilization significantly affected the number of functional microbes, Azotobacter and Phosphate Solubilizing Microbes (MPF). In addition, N uptake of sorghum and dry weight of sorghum seeds increased significantly by 5.54 times and 2.29 times, respectively, from control when urea fertilizer was applied to 200 kg urea ha-1.